Natural uranium and thorium isotopes in sediment cores off Malaysian ports - Yusoff, Abdul Hafidz; Sabuti, Asnor Azrin; Mohamed, Che Abd Rahim (SpringerLink, 2015)

(untitled)
Sediment cores collected from three Malaysian marine ports, namely, Kota Kinabalu, Labuan and Klang were analyzed to determine the radioactivities of 234U, 238U, 230Th, 232Th and total organic carbon (TOC) content. The objectives of this study were to determine the factors that control the activity of uranium isotopes and identify the possible origin of uranium and thorium in these areas. The activities of 234U and 238U show high positive correlation with TOC at the middle of sediment core from Kota Kinabalu port. This result suggests that activity of uranium at Kota Kinabalu port was influenced by organic carbon. The 234U/238U value at the upper layer of Kota Kinabalu port was ≥1.14 while the ratio value at Labuan and Klang port was ≤ 1.14. These results suggest a reduction process occurred at Kota Kinabalu port where mobile U(VI) was converted to immobile U(IV) by organic carbon. Therefore, it can be concluded that the major input of uranium at Kota Kinabalu port is by sorptive uptake of authigenic uranium from the water column whereas the major inputs of uranium to Labuan and Klang port are of detrital origin. The ratio of 230Th/232Th was used to estimate the origin of thorium. Low ratio value (< 1.5) at Labuan and Klang ports support the suggestion that thorium from both areas were come from detrital input while the high ratio (> 1.5) of 230Th/232Th at Kota Kinabalu port suggest the anthropogenic input of 230Th to this area. The source of 230Th is probably from phosphate fertilizers used in the oil-palm cultivation in Kota Kinabalu that is adjacent to the Kota Kinabalu port.